In vitro Digestion Characteristics of Hydrolyzed Infant Formula and Its Effects on the Growth and Development in Mice - Feng, Lifang; Ye, Wei; Zhang, Kuo; Qu, Daofeng; Liu, Weilin; Wu, Min; Han, Jianzhong (Frontiers in Nutrition, 2022)
Infant formula, an important food for babies, is convenient and nutritious, and hydrolyzed formulas have attracted much attention due to thier nonallergicity. However, it is uncertain whether hydrolyzed formulars cause obesity and other side effects in infants. Herein, three infant formulas, standard (sIF), partially hydrolyzed (pHIF), and extensively hydrolyzed (eHIF), were analyzed in an in vitro gastrointestinal digestion model. With increasing degree of hydrolysis, the protein moleculars and allergenicity of the proteins decreased and the long-chain polyunsaturated fatty acid content increased. Moreover, the digestion model solutions quickly digested the small fat globules and proteins in the hydrolyzed formula, allowing it to become electrostaticlly stable sooner. The eHIF-fed mice presented larger body sizes, and exhibited excellent exploratory and spatial memory abilities in the maze test. Based on villus height and crypt depth histological characterizations and amplicon sequencing, eHIF promoted mouse small intestine development and changed the gut microbiota composition, eventually favoring weight gain. The mouse spleen index showed that long-term infant formula consumption might be detrimental to immune system development, and the weight-bearing swimming test showed that eHIF could cause severe physical strength decline. Therefore, long-term consumption of infant formula, especially eHIF, may have both positive and negative effects on mouse growth and development, and our results might shed light on feeding formula to infants.